ENVIRONMENTAL MANAGEMENT CONTRIBUTED TO STUDENT LEARNING OF TRIAMUDOMSUKSA PHATTHANAKARN NONTHABURI SCHOOL UNDER THE JURISDICTION OF SECONDARY EDUCATION SERVICE AREA OFFICE 3 - Wonganutararoj, Preeyaporn; Ninsangrat , Navin; Wongin, Thonglor (Journal of MCU Nakhondhat, 2022)
The objectives of this research were to: 1) study environmental management contributed to student learning of Triamudomsuksa Phatthanakarn Nonthaburi school and 2 ) to compare environmental management contributed to student learning of Triamudomsuksa Phatthanakarn Nonthaburi school classified by genders and class levels. The population consisted of 436 students who studied in Mathayom 1-6 of Triamudomsuksa Phatthanakarn Nonthaburi school under the jurisdiction of secondary education service area office 3 in the academic year 2020.The sample size was determined by Krejcie & Morgan. The samples were 205 persons selected by strata and simple random samplings. The instruments used in this research was the questionnaire with the consistency was between 0.80-1.00 over and the reliability of .89. The statistics used for data analysis were frequency, percentage, mean, standard deviation, t-test, and Paired test of Scheffe’ s method.The research results revealed that:1) environmental management contributed to student learning as a whole and each aspects were at much level. When considering each aspect found that the majority were at much level by ascending order in administration aspect and academic management and physical aspect. 2) Students with different genders showed as a whole and each aspect were no different and 3) Students with different class levels showed opinions on environmental management contributed to student learning and the overall and each aspects were with statistically significant level of .05